PEMBUKTIAN DALAM KES HARTA SEPENCARIAN DI MAHKAMAH SYARIAH DI MALAYSIA - Md Noor, Ruzman (Jurnal Syariah, 2019)
This article tries to analyze the applicability of evidence in the issue of joint acquired property in Shariah Court in Malaysia. The research focuses on three elements, namely, the burden of proof, degree of proof and methods of proving. The study is based on the cases reported solely in Jurnal Hukum. The party who claims his or her contribution in obtaining the dispute property has to prove the claim. The main issues that have to be proved are; the existence of the said property, direct/indirect contribution and the amount of contribution. Their direct or indirect contribution, have to be proved through oral evidence, documentary evidence, bayyinah or shahadah and they have to attain at least the degree of ?an or balance of probalities in convincing the Court.